SCREENING OF MEDICINAL AND AROMATIC PLANTS OF HIMACHAL PRADESH FOR ANTIPROLIFERATIVE ACTIVITIES AGAINST BUDDING YEAST SACCHAROMYCES CEREVISIAE - ANIL KUMAR,; KAMAL DEV,; ANURADHA SOURIRAJAN, (International Journal of Pharma and Bio Sciences, 2015)
Medicinal plants contain a lot of bioactive compounds having various activities against human diseases. Based on traditional knowledge 62 plants (including 46 medicinal, 2 aromatic and 14 non medicinal plants) belonging to 38 families were collected from different regions of Himachal Pradesh. The plants from Himalayan region were tested for their anti-proliferative activities by using Saccharomyces cerevisiae as a drug discovery tool. The ethanolic extracts and essential oils of different plant parts such as flowers, leaves, fruit and rhizome were tested for anti-proliferative activity against budding yeast using agar well diffusion assays. Amongst the tested plants, Curcuma longa (rhizome) (Zingiberaceae) showed highest anti-proliferative effect with a zone of clearance of 26 mm and found fungicidal for yeast growth. Chrysanthemum indicum (leaves) (Asteraceae) exhibited anti-proliferative activity, with zone of clearance of 19.5 mm and fungistatic effect. In comparison, Aegle marmelose (leaves) (Rutaceae) showed least anti-proliferative effect, with zone of clearance of 18.5 mm and found fungicidal. The essential oils of Cymbopogon citratus and Rosmariuns officinalis also exhibited strong anti-proliferative effects against yeast growth. The phytochemicals of these plants responsible for anti-proliferative effect in yeast can be purified and explored for anticancer potential in humans.